R^2=(96/2)^2+14^2
r^2=2500
r=√2500
r=50
Answer:
4
Step-by-step explanation:
Although you didn't give me any answers to go with your problem, I am assuming that since 15-7 is 8, and 3 + 1 = 4, the answer should be 4. Now regarding if it is times, it would be x2. Because for times 2 would be 8. Overall the answer should be 4.
Answer:
<h2>A)x=3/2 y=½</h2>
Step-by-step explanation:
<h3>to understand this</h3><h3>you need to know about:</h3>
- system of linear equation
- PEMDAS
<h3>let's solve:</h3>
- since y is equal to both equation therefore we can substitute the value of y into the other equation
![\sf substitute \: the \: value \: of \: y : \\ \sf - x + 2 = 3x - 4](https://tex.z-dn.net/?f=%20%5Csf%20substitute%20%5C%3A%20the%20%5C%3A%20value%20%5C%3A%20of%20%5C%3A%20y%20%3A%20%20%5C%5C%20%20%5Csf%20%20-%20x%20%2B%202%20%3D%203x%20-%204)
![\sf add \: x \: to \: both \: sides : \\ \sf - x + x + 2 = 3x + x - 4 \\ \sf 4x - 4 = 2](https://tex.z-dn.net/?f=%20%5Csf%20add%20%5C%3A%20x%20%5C%3A%20to%20%5C%3A%20both%20%5C%3A%20sides%20%3A%20%20%5C%5C%20%20%5Csf%20%20-%20x%20%2B%20x%20%2B%202%20%3D%203x%20%2B%20x%20-%204%20%5C%5C%20%20%5Csf%204x%20-%204%20%3D%202)
![\sf add \: 4 \: to \: both \: sides : \\ \sf xx - 4 + 4 = 2 + 4 \\ 4x = 6](https://tex.z-dn.net/?f=%20%5Csf%20add%20%5C%3A%204%20%5C%3A%20to%20%5C%3A%20both%20%5C%3A%20sides%20%3A%20%20%5C%5C%20%20%5Csf%20xx%20-%204%20%2B%204%20%3D%202%20%2B%204%20%5C%5C%204x%20%3D%206)
![\sf divide \: both \: sides \: by \: 4 : \\ \frac{4x}{4} = \frac{6}{4} \\ x = \frac{3}{2}](https://tex.z-dn.net/?f=%20%5Csf%20divide%20%5C%3A%20both%20%5C%3A%20sides%20%5C%3A%20by%20%5C%3A%204%20%3A%20%20%5C%5C%20%20%5Cfrac%7B4x%7D%7B4%7D%20%20%3D%20%20%5Cfrac%7B6%7D%7B4%7D%20%20%5C%5C%20x%20%3D%20%20%5Cfrac%7B3%7D%7B2%7D%20)
let's figure out y
- substitute the got value of x into the second equation: y=3*3/2 -4
- simplify multiplication:9/2 -4
- simplify division:4.5-4
- substract:0.5 alternate form:y=½
Answer:
Step-by-step explanation:
JT = 19. 3(4) + 7
37 = CJ + JT
37 = 3x + 6 + 3x + 7
37 = 6x + 13
24 = 6x
X = 4
Answer:
g (f (-3)) = -9
Step-by-step explanation:
Given:
Graphs of f(x) and g(x) are given
From the given graphs:
Finding g ( f (-3) ):
-----> g ( f (-3) )
-----> g(5)
-----> -9
so,
g ( f (-3) ) = -9